Structural transitions and dipole moment of water clusters (H2 O) n=4-100 - Gelman Constantin, Julián (2010)
The properties of water clusters (H2 O) n over a broad range of sizes (n=4-100) were studied by microcanonical parallel tempering Monte Carlo and replica exchange molecular dynamics simulations at temperatures between 20 and 300 K, with special emphasis in the understanding of relation between the structural transitions and dipole behavior. The effect of the water interaction potential was analyzed using six nonpolarizable models, but more extensive calculations were performed using the TIP4P-ice water model. We find that, in general, the dipole moment of the cluster increases significantly as the cluster melts, suggesting that it could be used to discriminate between the solidlike and liquidlike phases. The effect of a moderate electric field on the cluster heat capacity and total dipole moment was found to be negligible.